2014
DOI: 10.4037/ccn2014262
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Evidence to Guide Practice: Challenging Practice Habits

Abstract: I n 2001, the Institute of Medicine challenged all health care professionals to decrease variation in practice through adoption of practice interventions based on best evidence to improve patients' outcomes.1 Current reviews of clinical practice suggest that only 10% to 15% of clinicians consistently implement evidence-based care 2 and indicate that it may take up to 2 decades for original research to be put into routine clinical practice.3 It is well established that evidence-based practice (EBP) is associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0
10

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 130 publications
(272 reference statements)
1
15
0
10
Order By: Relevance
“…A US study found that nurses in a hospital setting followed traditional practices, which were in opposition to the best evidence available. [18] Clinical decisions that are not based on evidence could be detrimental to the care of the critically ill patient. Gerrish and Cooke [11] found that the highest-ranked sources were tradition or ritual, intuition, information obtained from peers or colleagues and information from policy/ procedure manuals.…”
Section: Discussionmentioning
confidence: 99%
“…A US study found that nurses in a hospital setting followed traditional practices, which were in opposition to the best evidence available. [18] Clinical decisions that are not based on evidence could be detrimental to the care of the critically ill patient. Gerrish and Cooke [11] found that the highest-ranked sources were tradition or ritual, intuition, information obtained from peers or colleagues and information from policy/ procedure manuals.…”
Section: Discussionmentioning
confidence: 99%
“…Critical care nurses are in an optimal position to lead practice, moving traditions "out to pasture" and embracing EBP interventions. 1,2,12,[19][20][21][22][23][24] Through the multiple presentations and publications on these sacred cow practice traditions, clinical experts have challenged each of us to critically examine our practice and ensure that we are current, that our care is evidence based. This series is being retired because few new practice traditions or topics are arising.…”
Section: Discussionmentioning
confidence: 99%
“…When asking questions is encouraged, traditions in practice can be challenged, providing an opportunity to advance learning and practice through a culture that embraces EBP. [19][20][21][22][23][24] Ensuring that critical care nursing practice is based on the current best evidence supports a culture of safety, helping achieve the goal of excellent care for every patient, every time.…”
Section: Evidence-based Practice and Highreliability Organizations: Smentioning
confidence: 99%
See 2 more Smart Citations